IDENTIFIKASI KEBERADAAN COLIFORM DAN E. coli PADA AIR BERSIH DI PELABUHAN TANUNG EMAS SEMARANG - Ayu Widyawati; Tri Joko; Onny Setiani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
One of the water treatment efforts is disinfection. Disinfection aims to kill pathogenic microorganisms that can cause health problems for humans. One of the disinfectants that is commonly used is chlorine because chlorine is easily available and affordable. The use of chlorine as a disinfectant must meet the appropriate dosage requirements and techniques. Pelindo Semarang reservoir is disinfected with 250 grams of chlorine and is repeated once a month. This study aimed to identify Total Coliform and E. coli on the day immediately after affixing, 7th, 14th, 21st and 28th days at the Pelindo Reservoir, Nusantara Pier Hydrant, Passenger Terminal Reservoir, Samudera Pier Hydrant, TPKS Pier Hydrant and TPKS Reservoir. Result found that the condition of the Pelindo Reservoir as the main reservoir in an open state, there is garbage around the reservoir and no drainage is carried out. Total Coliform meets the quality standard of 16.7%. Meanwhile, E. coli meets the quality standard of 13.3%. Addition of chlorine at one time is considered less effective in reducing coliforms or eliminating E coli.